Current clinicopathological characterisation of adamantinoma - a review of the literature - Węgrzyniak, Agata; Wokurka, Wojciech; Drobek, Dominik; Winiarz, Aleksandra; Szlendak, Paula; Toś, Katarzyna; Wojtala, Kacper; Turek, Michał; Wąsala, Katarzyna; Grosman, Sylwia (Journal of Education, Health and Sport, 2023)
Introduction and purpose Adamantinoma is an exceedingly rare, primary bone tumour, that in most cases affects the diaphysis of the long bones, especially the tibia. Histologically it is epithelial cells clusters surrounded by spindle-cell osteofibrous components. Adamantinoma has metastatic potential to the lungs and local lymph nodes. Both the rarity of the disease and its nonspecific symptoms complicate diagnosis and treatment. Reviewing the up-to-date data regarding adamantinoma was the purpose of the work. State of knowledge During the 5th edition of the World Health Organization (WHO) classification of bone tumours in 2020 adamantionoma was classified in the newly established bone tumour class of the other mesenchymal tumours of bone. What is more its name was specified to adamantionoma of the long bone. According to literature and newest classification adamantinoma is divided into 3 types; the most common classic adamantinoma as well as less frequent OFD-like adamantinoma (osteofibrous like adamantinoma) and dedifferentiated adamantinoma. Diagnosis is challenging due to the rarity of occurrence, insufficient knowledge and misinterpretation of imaging studies resulting in the diagnosis of adamantinoma as other bone and soft tissue tumours. Conclusions Confirmation of the immunohistochemical profile, as well as the genetic profile of adamantionoma, which are increasingly well-defined, is essential for diagnosis. Imaging studies still remain the first method used in the diagnostic process. MRI appears to be the most suitable method for the imaging diagnosis of adamantinoma, due to excellent imaging of the tumour extent, including its surrounding soft tissue involvement and possible metastases. As far as treatment is concerned, there are still no precise guidelines and the best option remains tumour resection with large margins